Secondhand Smoke Exposure and Brain Health Indicators in Cuban Preschoolers - Yaser Ramírez Benítez; Miriela Díaz Bringas; Rodneys Mauricio Jiménez-Morales; Ijang Bih Ngyah-Etchutambe; Linda S. Pagani (Toxics)
Secondhand smoke affects nearly 40% of children worldwide, leading to serious health and behavioral problems. Being neurotoxic, it poses potential risks for child health and learning. In Cuba, there is limited research on the association of secondhand smoke with children’s brain health, especially in vulnerable populations like young children at home. The overall purpose of this study is two-fold. First, we determined the relationship between household smoke exposure and risks to brain health in Cuban children. Second, we analyzed the role of family environment factors, such as socio-economic status, in our estimates. Although this research represents the first investigation of its kind in Cuba, we expect to find evidence of neurotoxic associations with household smoke. We collected data between 2015 and 2018 using the medical records of 627 Cuban preschool children to explore the link between brain health indicators and exposure to tobacco smoke at home. We assessed archival reports on parental smoking, duration and frequency of exposure, and several indicators of brain health, including executive function, language development, sleep quality, and fluid intelligence. The findings indicate that exposure to tobacco smoke at home has a negative association with children’s brain health, affecting both the cognitive (executive and linguistic functions) and non-cognitive aspects (sleep quality) of child development. Continuous exposure (five to seven times per week) and transient exposure (two to three times per week) were found to be more negatively related to sleep quality than in cognitive functions, particularly in children of middle socio-economic status. This highlights the need to implement parental information campaigns in Cuba.